Desafios metodológicos na perspectiva da rede de significações Methodological challenges from a perspective of net of meanings - Maria Clotilde Rossetti-Ferreira; Kátia de Souza Amorim; Ana Paula Soares-Silva; Zilma de Moraes Ramos de Oliveira (Cadernos de Pesquisa, 2008)
O trabalho busca explicitar alguns dos pressupostos da perspectiva teórico-metodológica denominada Rede de Significações. Inicialmente utilizada para a investigação do desenvolvimento humano, ela tem sido incorporada em estudos sobre educação e saúde e em temáticas variadas. Especificamente, o texto procura explorar questões metodológicas assim como os referenciais com os quais essa perspectiva dialoga. Partindo de uma contextualização dos paradigmas que compreendem os fenômenos em sua complexidade, discutem-se os desafios encontrados pelo pesquisador na análise de um conjunto de elementos de ordem pessoal, relacional e contextual que interagem na realidade investigada. Postula-se a necessidade de uma dialética que contemple a descrição de uma microistória dos processos que seja interpretável de uma perspectiva semiótica e considere as condições mais amplas da cultura e da história. Discute-se ainda a relação sujeito-objeto de observação/investigação e o papel ativo do pesquisador, compreendido como um ferramenteiro, nos estudos empíricos. This work seeks to clarify some of the assumptions of the theoretical-methodological perspective known as Net of Meanings which was initially used to investigate human development and lately has been incorporated into studies about education, health, and other subjects. Specifically, the text looks into methodological issues arising from its appropriation, as well as from the referentials with which this perspective holds a dialogue. Starting from the contextualization of paradigms which includes the phenomena in their complexity, in their transformation processes and that are systematically constituted by multiple dimensions, the challenges the researcher comes across are discussed in the analysis of the set of elements of personal, relational, and contextual order which interacts in the reality being investigated. Our assumption is that there is a need for a dialectical approach that contemplates the description of a micro history of the processes which can be interpreted from a semiotics perspective and which takes into account the most comprehensive conditions of culture and history. The relationship between the subject-object of the observation/investigation and the active role played by the researcher, who is seen as a toolmaker in the empirical studies, is also discussed.